The Effect of Participatory Budgeting, Organizational Commitment, on the Effectiveness of the Implementation of Responsibility Accounting, and Its Implications on Managerial Performance (A survey of PT BUMNIS in West Java) - Syafdinal; Irawati, Erni; Mulyanti Fauziah, Siti; Sugiarti, Irna; Octavia, Tressa (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the manager's performance for the Strategic Industrial State-Owned Enterprises (BUMNIS) in the effort to achieve the goals to be addressed, it is necessary to conduct research on the performance of managers in the three BUMNIS and participatory budgeting, and organizational commitment and effectiveness of the implementation of responsibility accounting that affects it. This research is an explanatory research. Data were collected by survey method using a questionnaire of 61 respondents. Hypothesis testing using SEM analysis. The results of calculations performed using the LISREL program. The results showed that the direct and indirect effects of participatory budgeting and organizational commitment to the variable: the effectiveness of the implementation of accountability accounting by 53%. Direct and indirect effects Participatory budgeting, and organizational commitment, on variables: managerial performance of 59.3%. The effect of the effectiveness of the implementation of responsibility accounting on managerial performance by 38%.